Near Full-length Genomic Sequencing and Molecular Analysis of HIV-Infected Individuals in a Network-based Intervention (TRIP) in Athens, Greece: Evidence that Transmissions Occur More Frequently from those with High HIV-RNA - Kostaki, Evangelia-Georgia; Frampton, Daniel; Paraskevis, Dimitrios; Pantavou, Katerina; Ferns, Bridget; Raffle, Jade; Grant, Paul; Kozlakidis, Zisis; Hadjikou, Andria; Pavlitina, Eirini; Williams, Leslie D.; Hatzakis, Angelos; et al. (Current HIV Research, 2018)
Background: TRIP (Transmission Reduction Intervention Project) was a network-based, contact tracing approach to locate and link to care, mostly people who inject drugs (PWID) with recent HIV infection. Objective: We investigated whether sequences from HIV-infected participants with high viral load cluster together more frequently than what is expected by chance. Methods: Paired end reads were generated for 104 samples using Illumina MiSeq next-generation sequencing. Results: 63 sequences belonged to previously identified local transmission networks of PWID (LTNs) of an HIV outbreak in Athens, Greece. For two HIV-RNA cut-offs (105 and 106 IU/mL), HIV transmissions were more likely between PWID with similar levels of HIV-RNA (p<0.001). 10 of the 14 sequences (71.4%) from PWID with HIV-RNA >106 IU/mL were clustered in 5 pairs. For 4 of these clusters (80%), there was in each one of them at least one sequence from a recently HIVinfected PWID. Conclusion: We showed that transmissions are more likely among PWID with high viremia.
Keywords: PWID